Framing renewable energy - Bolsen, Toby (Nature energy, 2022)
Understanding how beliefs about renewable energy sources are influenced by exposure to information is important for the successful implementation of policies to combat climate change. New longitudinal research shows that messages emphasizing specific benefits of renewable energy can exert a lasting impact on partisans’ beliefs.